A Case Study on the Impact of Crosswalk Markings on Driver Yielding to Pedestrians. (November 2019) - Craig, Curtis M.; Morris, Nichole L.; Hong, Yubin
The research team measured yielding at marked, unsignalized crosswalks as part of a multifaceted high visibility enforcement intervention intended to improve pedestrian safety. One of the crosswalks had its markings removed. With concern to possible reduced driver expectancy for pedestrians after the removal of the crosswalk, measurement continued at that location as a case study on the impact of crosswalks on drive yielding on multilane roads. Measurement of yielding at the unmarked crosswalk, when compared to similarly marked crosswalks, observed less yielding overall and more yielding at closer distances to the unmarked crosswalk, which poses a significant risk to pedestrians. The findings have implications for traffic infrastructure planners attempting to optimize safety for pedestrians.